2022
DOI: 10.4274/jcrpe.galenos.2022.2022-4-24
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Levels of Spexin, Leptin, and Visfatin in Term Infants Born Small, Appropriate, and Large for Gestational Age and Their Association with Newborn Anthropometric Measurements

Abstract: Objective: Children born small for gestational age (SGA) are at risk of future obesity and associated comorbidities. Therefore the identification of risk factors and novel biomarkers which are associated with this risk are needed for early detection and to improve preventive strategies. Spexin (SPX), a novel neuropeptide that is involved in the regulation of obesity and fat metabolism, is a candidate biomarker for predicting obesity and related comorbidities at an early age. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…On the same hand, Mazaki-Tovi et al compared the levels of maternal serum visfatin in 158 normal pregnancies with the levels of maternal serum visfatin levels in 55 women who delivered SGA infants and concluded that maternal visfatin levels were higher in pregnancies with SGA infants than in normal pregnancies. Pekal et al measured maternal visfatin concentration in 40 women with SGA neonates and compared it with visfatin concentration in 40 women with AGA neonates, and in contrast with the above, came to the conclusion that visfatin concentration levels were significantly lower in mothers with SGA infants than in mothers with AGA infants [ 19 , 20 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the same hand, Mazaki-Tovi et al compared the levels of maternal serum visfatin in 158 normal pregnancies with the levels of maternal serum visfatin levels in 55 women who delivered SGA infants and concluded that maternal visfatin levels were higher in pregnancies with SGA infants than in normal pregnancies. Pekal et al measured maternal visfatin concentration in 40 women with SGA neonates and compared it with visfatin concentration in 40 women with AGA neonates, and in contrast with the above, came to the conclusion that visfatin concentration levels were significantly lower in mothers with SGA infants than in mothers with AGA infants [ 19 , 20 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“… Newcastle–Ottawa scale (NOS) quality assessment of the included studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].√: the criterion under question is met, √√: two adjusting factors were taken into consideration. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge concerning the leptin level in maternal–infant dyads, similar to adiponectin, is fragmentary. So far, only nine reports have presented data on the leptin levels for two different biological samples (maternal and cord plasma) [ 77 , 115 , 116 , 117 , 118 , 120 , 121 , 122 , 123 ], and two simultaneously characterize the leptin status in three different biological fluids: maternal plasma, cord plasma, and milk ( Table 3 ) [ 113 , 119 ].…”
Section: Adipokines In Maternal–infant Dyadmentioning
confidence: 99%
“…Pekal and coworkers [ 122 ] analyzed the leptin levels in maternal and cord serum depending on birth weight and their association with the newborn’s anthropometric measurements. Pekal’s group identified significant differences in the cord serum leptin levels among the term-born small for gestational age (SGA) (3.5 ng/mL), appropriate for gestational age (AGA) (6.3 ng/mL), and large for gestational age (LGA) (9.8 ng/mL) groups.…”
Section: Adipokines In Maternal–infant Dyadmentioning
confidence: 99%